Currency and Stock Exchanges: on the Efficiency Shoals - Rutkauskas, Aleksandras Vytautas; Kaleininkaitė, Laura (Ekonomika, 2005)
The purpose of this article is to define the preliminary results of investigation of decision-making management in currency and stock exchanges. The object of the research is decision-making management in currency and capital markets. A particular aim of the research has been creation and practical utilization of a currency and stock trading system which relies upon historical data and provides for trading strategies with a guarantee ensuring positive trading results. The conceptual aim of the paper is to show (according to specially elaborated simple portfolio trading strategies) that today’s currency exchange rate and capital markets offer real possibilities to get a bigger than average trading profit, i.e. to show that in these markets there are some “shoals” of effectiveness, which can be realized as inefficiency features of these markets.